Recent advances in exploring and exploiting soybean functional peptides—a review - Zhu, Yongsheng; Chen, Gang; Diao, Jingjing; Wang, Changyuan (Frontiers in Nutrition, 2023)
Soybean is rich in proteins as well as phytochemicals like isoflavones and phenolic compounds. It is an excellent source of peptides that have numerous biological functions like anti-inflammatory, anti-cancer and anti-diabetic activities. Soy bioactive peptides are small building blocks of proteins that are mainly released after fermentation or gastrointestinal digestion, but also by food processing through enzymatic hydrolysis often in combination with novel food processing techniques (i.e., microwave ultrasound, and high-pressure homogenization), which are linked to numerous health benefits. Various studies have reported potential health benefits of soybean-derived functional peptides, which have made them a great substitute for many chemical-based functional elements in foods and pharmaceutical products for a healthy lifestyle. In this review, some unprecedented and the most up-to-date insights into the role of soybean peptides against various diseases and metabolic disorders ranging from diabetes and hypertension to neurogenerative disorders and viral infections with mechanisms were discussed. In addition, we have discussed all known techniques, including conventional and emerging approaches, for the prediction of active soybean peptides. Lastly, some real-life applications of soybean peptides in food and pharmaceutical products as functional entities were discussed.